The Correlation of Serum Total Testosterone, Sex Hormone Binding Globulin and Free Androgen Index with Athens Insomnia Scale Score in Polycystic Ovary Syndrome - Hartanto Bayuaji; Heda Melinda Nazaruddin Nataprawira; Herri Suhari Sastramihardja (The Indonesian Biomedical Journal, 2018)
BACKGROUND: Polycystic ovary syndrome (PCOS), a common reproductive endocrinologic disorder in woman, was considered to be related to sleep disturbance. This study is aimed to analyze the correlation between excess androgen markers and Athens Insomnia Scale (AIS) in PCOS.METHODS: This observational, cross-sectional study of PCOS was conducted to 31 subjects to evaluate the correlation between serum total testosterone, sex hormone binding globulin (SHBG) and free androgen index with the incidence of sleep disturbance using AIS. Sleep disturbance was present if the score ≥6. The correlation between excess androgen markers and sleep disturbance was analyzed using Pearson’s coefficient of correlation or Spearman’s rho test. Correlation coefficient more than 0.5 with p<0.05 was considered significant.RESULTS: Out of 31 PCOS subjects aged 20-40 years, 39% subjects had AIS score ≥6. Mean serum testosterone in AIS score >6 group was higher than AIS score <6 group but not statistically significant (46.68 vs. 28.49 ng/mL, p>0.05). No significant correlation was found between serum total testosterone, SHBG and free androgen index with AIS score. After adjusting for AIS score, there was the moderate positive correlation between serum total testosterone level although not statistically significant (r=0.54, p=0.07).CONCLUSION: The serum total testosterone level might influence the occurrence of sleep disturbance in PCOS.KEYWORDS: PCOS, androgen excess, testosterone, sleep disturbance, Athens Insomnia Scale